2013
DOI: 10.1021/ef400198v
|View full text |Cite
|
Sign up to set email alerts
|

Polygeneration of Liquid Fuels and Electricity by the Atmospheric Pressure Hybrid Solar Gasification of Coal

Abstract: An analysis of system operation and performance has been undertaken, for the first time, of a solar-hybrid coal-toliquids polygeneration facility incorporating solar resource variability. The energetic and environmental performance of a coal-toliquids process that is integrated with a solar hybridized, oxygen blown, atmospheric pressure gasifier (CTL sol ) is compared with that of a reference, nonsolar, autothermal, pressurized gasification integrated, CTL ref configuration. To allow the plant to respond to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 51 publications
4
81
0
Order By: Relevance
“…Significant CH 4 was only observed in the experiments using lignite coal as the feedstock, possibly due to the higher volatile content and CH 4 being generated during pyrolysis. The highest = X 0.79, were observed for the activated charcoal under the high H 2 O:C conditions with O 2 where, presumably, full conversion did not occur due to entrainment of the smaller particles that did not fully react as observed after experimentation.…”
Section: Tablementioning
confidence: 94%
See 2 more Smart Citations
“…Significant CH 4 was only observed in the experiments using lignite coal as the feedstock, possibly due to the higher volatile content and CH 4 being generated during pyrolysis. The highest = X 0.79, were observed for the activated charcoal under the high H 2 O:C conditions with O 2 where, presumably, full conversion did not occur due to entrainment of the smaller particles that did not fully react as observed after experimentation.…”
Section: Tablementioning
confidence: 94%
“…Product gases were temporally monitored with a combination of mass spectrometry (MS, OmniStar ThermoStar GSD320 Gas Analysis System) and gas chromatography (GC, Agilent 490 Micro GC equipped with Molsieve and PoraPLOT Q columns). The GC was calibrated for H 2 , CO, CO 2 , CH 4 , and O 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have investigated the key drivers of the amount of energy storage required to integrate CST collectors with power generation [1][2][3][4][5][6][7] and fuel production cycles [8,9]. These analyses have largely been based on hybrid energy systems, where CST power is indirectly introduced through a secondary thermal loop [1][2][3][4][5][6] or the combustion of fossil fuels is either supplemented through the direct introduction of CST power into a thermochemical reactor [8], directly into a boiler volume to drive a power cycle [7]. These http://dx.doi.org/10.1016/j.apenergy.2016.04.067 0306-2619/Ó 2016 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…A recent full-year process modeling analysis of a system integrating an atmospheric pressure hybrid solar gasifier with a FT liquids production system, using an hourly averaged solar dataset, showed that as little as eight hours of syngas storage was required to enable steady state operation of the downstream syngas upgrading reactor over a full solar year [8]. This analysis proposed a hybrid, continuously operational solar, entrained flow gasifier based on the experimentally proven solar vortex reactor [11,12], assuming that CST power drives gasification in the reactor volume when it is available and autothermal reactions in pure O 2 drive gasification, within the same volume, when solar energy is not available [8].…”
Section: Introductionmentioning
confidence: 99%